Celebrating Uncertainty in Qualitative Research (KULT_online, 2013)
Edited by Maggi Savin-Baden and Claire Howell Major, New Approaches to Qualitative Research: Wisdom and Uncertainty offers a relevant contribution to the field of qualitative inquiry by highlighting new, emerging approaches to qualitative research. The central guiding concepts of the book are wisdom and uncertainty and the volume is structured accordingly in three parts reflecting on wisdom that underlies uncertainties in stance, approach, and space. The topics addressed range from locating values and truths in qualitative research to questions about responsible ethics, from discussing the benefits of narrative theory and ethnodrama to a qualitative approach to questioning culture through the corporeal and exploring the politics of space. Although the vast majority of contributors come from educational or health research, the explorative approaches tackled here and ethical dilemmas related to a qualitative approach exceed disciplinary borders. This also justifies the editorial claim that the volume is intended for a specialist audience in a broad range of subject areas.